OPG-Fc Treatment in Growing Pigs Leads to Rapid Reductions in Bone Resorption Markers, Serum Calcium, and Bone Formation Markers - Sipos, W.; Zysset, P.; Kostenuik, P.; Mayrhofer, E.; Bogdan, C.; Rauner, M.; Stolina, M.; Dwyer, D.; Sommerfeld-Stur, I.; Pendl, G.; Resch, H.; Dall’Ara, E.; Varga, P.; Pietschmann, P. (Hormone and Metabolic Research, 2011)
Inhibition of the receptor activator of NF-κB ligand (RANKL) is a novel therapeutic option in the treatment of osteoporosis and related diseases. The aim of this study was to evaluate bone metabolism and structure in pigs after RANKL inhibition. 12 growing pigs were assigned to 2 groups with 6 animals each. The OPG group received recombinant human OPG-Fc (5 mg/kg IV) at day 0, the control group was given 0.9% NaCl solution. Serum levels of OPG-Fc, calcium (Ca), phosphorus (P), and bone turnover markers were evaluated every 5 days, and pigs were euthanized on day 20. Serum OPG-Fc concentration peaked at day 5 and coincided with significantly decreased Ca, P, and bone turnover markers. By day 15, measureable OPG-Fc serum levels could only be detected in 2/6 animals. With OPG-Fc clearance starting at day 10, serum Ca and P concentrations were not different between the 2 groups. TRACP5b, P1CP, and BAP levels significantly decreased by 40–70% relative to vehicle controls in the OPG-Fc group between days 5 and 10, indicating that pharmacologic concentration of OPG-Fc led to systemic concomitant inhibition of bone formation and resorption in young growing pigs. Dual X-ray absorptiometry data derived from the proximal femur did not differ between the 2 groups. μCT analysis of selected bone sites demonstrated an OPG-Fc-induced improvement of specific bone architectural indices and bone mineralization.
Keywords: bone metabolism; RANKL inhibition; trabecular architecture